Knowledge will set you free: Financial awareness and inclusion in the bottom of the pyramid - GHOSH, Aurobindo (Institutional Knowledge at Singapore Management University, 2016)
In this project, we explored whether financial literacy and economic awareness alleviates financial exclusion for the general population, particularly the financially underserved sections of the population in Ho Chi Minh City (HCMC) in Vietnam. We overcame the problem of identifying the financially excluded by looking at multiple measures of financial inclusion including frequency of bank use, access to borrowing for business, having a regular savings plan and having some insurance for possible future unfavorable outcomes. Using an innovative principal component (PCA) based method we identified a single score factor that can be construed as an overall measure of the degree of financial inclusion, using participation in the formal financial institutions and outlined the locations which is leading or lagging in financial inclusion. We determine factors including demographic, socio-economic, expectation or perception based and finally, accessibility and propensity for financial services based factors that influence measures of financial inclusion. We establish that factors including duration of stay, educational qualification, and in particular, keenness on getting more financial awareness and new innovative financial services, do indeed impact financial inclusion almost as much as income and other opportunities like education. We also propose an alternate and internal measure of financial inclusion in the budget share of necessities among individuals and identify channels that impact the budget share. Having established benchmark measures of financial inclusion we recommend possible technology-enabled policy based approach to accelerate financial inclusion in the bottom of the pyramid.